Special considerations concerning the use of antiretroviral drugs in children. Issue 12 (1st December 2016) - Frange, Pierre; Bouazza, Naïm; Fassinou, Patricia; Warszawski, Josiane; Blanche, Stéphane
ABSTRACT: I ntroduction : Antiretroviral therapy is extremely effective in both children and adults infected with HIV. Treatment indications have rapidly expanded; ideally, with rare exceptions, all infected children should now be treated. A reas covered : The use of antiretroviral drugs in children is based largely on extrapolations from experience with adult patients. Pharmacokinetic studies are required in addition to formal studies, which are difficult to conduct in pediatric situations, extending from birth to adolescence. However, despite often inadequate galenic formulation, treatment of children is easier than generally thought. No major or irreversible toxicity has been observed with the latest generation of molecules. Several observations suggest that very early treatment, beginning shortly after birth, provides better long-term immunological control of infection. E xpert commentary : All HIV-infected children should be treated with antiretroviral drugs. Manufacturers should propose appropriate dosage forms, including combined forms in particular, and should support pharmacological and tolerance studies in pediatric patients of various ages. Very early treatment maximizes the chances of long-term immunological control.